Identification of Stakeholder Involvement in Decision-Making Needs (Case Study: Sanur Port Construction Project) - Wijanarko, Heru; P., Rani Gayatri Kusumawardhani; Puri, Eliza Rosmaya (Journal of Applied Sciences, Management and Engineering Technology, 2024)
This study aims to identify the priority weight in decision-making in the Sanur Port construction project, which involves various stakeholders with diverse interests and powers. Decisions taken in this project can determine the success of implementation and reduce the impacts caused, especially in dealing with problem situations. The study was conducted using a focus group discussion method involving experts who are experienced in port development. Furthermore, the Rank Order Centroid (ROC) method was used to calculate the priority weight of each stakeholder in decision-making according to expert opinion. The results of the study showed that 11 stakeholders were collected into 4 quadrants in the stakeholder mapping. The highest priority weight is acquired by the project owner (0.5467), JO - planning consultant contractor (0.2567), and construction management consultant (0.1566), which are in quadrant 1, followed by the local government (0.0900) in quadrant 2, and the affected community (0.0400) which is a combination of quadrants 3 and 4. This finding indicates that in decision-making in the Sanur Port construction project, a diverse approach is needed to minimize losses from each stakeholder. The results of this study are expected to offer insight for decision-makers to understand the dynamics of stakeholders in port construction projects. This understanding will help improve the effectiveness of project management in the future.